EFEKTIVITAS TEKNIK SELF MANAGEMENT UNTUK MENGATASI PERILAKU PROKRASTINASI AKADEMIK - Fadhillah, Nurul; Asrori, Muhamad; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to examine the effectiveness of self-management techniques in eliminating academic procrastination in class VIII students of SMP Negeri 18 Pontianak. The research method used is quantitative in the form of a Pre-Experimental Design research with a Pre-test "“ Post-test One Group Design research design. The total population is 198 students. The sampling technique used was the purposive sampling technique, the sample size was 12 students with high levels of procrastination. Based on the calculations, the average pre-test before being given treatment was 97 and the post-test after being given treatment was 59. Then, the T count was obtained using the Paired Sample T-test sample, namely 18,709 with a sig. (2 tailed) 0.00 0.05 which means H0 is rejected and Ha is accepted, thus there is a significant difference in student academic procrastination before and after being given Self Management. So it can be concluded that the Self Management technique is effective for eliminating academic procrastination in class VIII students of SMP Negeri 18 Pontianak